Cortisol predicts migration timing and success in both Atlantic salmon and sea trout kelts - Birnie-Gauvin, Kim; Flávio, Hugo; Kristensen, Martin L.; Walton-Rabideau, Sarah; Cooke, Steven J.; Willmore, William G.; Koed, Anders; Aarestrup, Kim (Scientific reports, 2019)
Kelts – individuals of anadromous fish species which have successfully spawned and may return to sea to repeat the cycle – are perhaps the least studied life stage of iteroparous fish species. To date, our understanding of what makes them successful in their return migration to sea is limited. We investigated the relationship between three physiological parameters (baseline cortisol, baseline glucose and low molecular weight antioxidants) and the timing and success of Atlantic salmon ( Salmo salar ) and sea trout ( Salmo trutta ) kelt migration. To do so, we combined blood samples obtained within 3 minutes of capture and acoustic telemetry to track 66 salmon and 72 sea trout as they migrated out of rivers, into fjords and out at sea. We show that baseline cortisol may be a good predictor of migration success. Individuals with high baseline cortisol levels exited the river earlier but were less likely to successfully reach the sea. Similar relationships were not observed with glucose or antioxidants. We provide the first evidence to support the role of physiological status in migration success in Atlantic salmon and sea trout kelts. Our findings contribute to our understanding of the relationship between physiology and fitness in wild animals. Further, we suggest that migration timing is a trade-off between stress and readiness to migrate.